Penggunaan Smartphone dan Perilaku Sosial Anak Usia Dini: A Correlational Study - Wahyudi, Hendro; Sari, Niken Ayu Merna Eka (STAI Auliaurrasyidin Tembilahan, 2024)
A smartphone is a communication tool that has various features. Smartphone users do not only come from workers but children and toddlers. The use of smartphones, especially in early childhood, has multiple negative impacts – besides its positive impacts - such as decreased concentration while learning, causing health problems, slowing cognitive development, and affecting the formation of social behavior. In line with that, this study aims to determine the relationship between smartphone use and the formation of social behavior in early childhood. This study used a descriptive correlational design with a cross-sectional approach. The population used in this study was 108 parents, while the sample amounted to 85 parents which is taken using the purposive sampling technique. Data were collected using questionnaires about smartphone use and children’s social behavior. The data were then analyzed using the Spearmen rank correlation test with a significance of p < 0.05. The results of this study indicate that the use of smartphones is related to the formation of social behavior in early childhood, with a correlation strength value of 0.798 (correlation strength = strong).